Staples, Political Economy and Trade Flows: A New Interpretation and Quantitative Evidence - Holmes, Gordon O. (My University, 2013)
The first section of this thesis identifies two schools of economic thought that were prominent between 1923 and the 1960s. Both employed a staples approach to organize, explain and interpret Canada’s history but used different scopes of inquiry, methodologies and time horizons. I call these two schools Innis’ staples thesis and Macintosh’s staple economics. No sooner were these two schools firmly established than the economics profession underwent a fundamental shift. Economic historians abandoned the old Canadian political economy in the 1960s and followed international trends toward increased specialization. Academic economists concentrated on theoretical and deductive methods with little concern for historical time. During this period of rapid transition, Mel Watkins developed a third approach known as the staple theory. If contemporary economists are cognizant of a staples approach, they most likely think about Watkins’ theory which was written during the ascendancy of the ‘new’ economic history in the United States.
One of the legacies of the old political economy was the construction of historical data sets, but they are rarely used in contemporary studies. The collection of historical data related to staples activity waned as the focus shifted to the construction of national accounts. The reconstruction of Canada’s trade flows was abandoned. The last five chapters of this thesis remedy this neglect with a new series of trade flows for all British North America from 1829 to 1960. Economic historians will now have a continuous series of meaningful trade statistics to facilitate future research on the role of staples in international economy of British North America. With this information, research can begin to evaluate the long-run evolution of the structure, behaviour and performance of Canada’s external economy from a simple colonial society to a modern industrial nation.
Keywords: Canadian Economic History; Intellectual History; Intellectual History